Survey participation as a function of democratic engagement, trust in institutions, and perceptions of surveys. (19th October 2022) - Silber, Henning; Moy, Patricia; Johnson, Timothy P; Neumann, Rico; Stadtmüller, Sven; Repke, Lydia
Abstract: Objective: With response rates of large‐scale surveys having decreased significantly over the years and rebounds seeming unlikely, many studies now examine how response rates vary with methodological design and incentives. This investigation delves into how individual‐level factors shape survey participation. Specifically, we examine the influence of individuals' democratic engagement and their trust in institutions on intent to participate in surveys, both directly and indirectly through their perceptions of surveys. Methods: We collected survey data from a probability sample of adults ( N = 1343) in Mannheim, Germany, from November 2019 to March 2020. Structural equation models were estimated to test the hypothesized relationships. Results: The analyses support most, but not all, hypothesized relationships. Democratic engagement bolstered intent to participate, directly as well as indirectly through perceptions of surveys. Institutional trust, on the other hand, only influenced the outcome measure indirectly. Perceptions of surveys had a strong bearing overall effect on intent to participate. Conclusion: The study's results suggest that the response rates and larger issues related to the perceived legitimacy of public opinion and survey research might be intertwined with orientations related to people's civic and political life. The article discusses potential ways survey researchers can counteract distrust in surveys.